Зоофразеологізми: походження та особливості - Ракітіна, В. О. (ХНУРЕ, 2022)
Zoophraseologism is a way of expressing traditions and cultural associations of the people. It carries an indirect meaning with the projection of the world of fauna on humans, playing a large role in semantics. Interestingly, cattle are most used in zoophraseologisms because such expressions are a reflection of contact with animals, namely with livestock, which ancestors contacted with daily.